2019
DOI: 10.1039/c8ta09713e
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the breathing phenomenon in ZIF-4

Abstract: The pufferfish effect in ZIF-4: synchrotron X-ray powder diffraction studies under operando conditions confirm that ZIF-4 experiences a breathing phenomenon above ∼30 kPa associated with a large expansion in the unit cell volume (∼8–9%). The presence of an expanded-pore (N2) ZIF-4 structure is predicted by molecular simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 15 publications
(30 reference statements)
3
31
0
Order By: Relevance
“…Developments in gas-handling systems have also paved the way to probe gate-opening and related network-breathing phenomena arising from the unique elastic properties of MOFs—see entries in Table 1 and Refs. [ 151 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: From Confined Polymers To Soft Supramolecular Frameworkmentioning
confidence: 99%
“…Developments in gas-handling systems have also paved the way to probe gate-opening and related network-breathing phenomena arising from the unique elastic properties of MOFs—see entries in Table 1 and Refs. [ 151 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: From Confined Polymers To Soft Supramolecular Frameworkmentioning
confidence: 99%
“…A variety of ZIFs have been reported in the literature including the commonly studied examples of ZIF-8, ZIF-7, and ZIF-4. , The framework topology of a ZIF depends upon the interplay between the nonbonding and the bonding interactions in the structure. Stronger nonbonded interactions favor the formation of high-density structures such as ZIF-7, while strong bonding interactions like bending and torsion tend to favor low-density structures such as the large pore form of ZIF-8 . These interaction energies are influenced by the choice of linker functionalization, which varies greatly among ZIFs .…”
Section: Introductionmentioning
confidence: 99%
“…The imidazolate rings can rotate about the nitrogen axis, causing the windows to open or close. As a result, like many other ZIFs, ZIF-4 can adsorb molecules with kinetic diameters larger than the PLD, such as n -alkanes and CO 2 . Gandara et al recently showed that the N 2 isotherm in ZIF-4 at 77 K shows multiple steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZIFs belong to MOFs microporous crystalline family and is the most primary of these structures because they have one un-substituted Imidazolate linkers. Pore size diameter of ZIF-4 is 0.21 nm windows with an orthorhombic spaces and cag network topology [25]. They have different application such as heterogeneous catalyze, gas separation and sensor because of their high chemical and thermal stability [26].…”
Section: Introductionmentioning
confidence: 99%